Keeping warfarin patients safe during the COVID-19 pandemic: review of an INR self-testing programme. (10th February 2022) - Gee, Emma; Pol, Angeline; Kittoe, Kwesi; Coker, Folusho; Speed, Victoria
Abstract : Background: Anticoagulation clinics faced an unprecedented challenge during the COVID-19 pandemic to safely manage patients on warfarin therapy. Methods: A London teaching hospital trust received INR point-of-care (POC) testing devices from its clinical commissioning group. The Trust distributed the devices to patients who were cognitively and physically able to self-test and evaluated clinical outcomes and patient experience. Findings: A significant improvement in warfarin control (mean time in therapeutic range (TTR) before POC 52%, standard deviation (SD) 24.8, vs mean after 60.7%, SD 19.7; P >0.009) and a 39% reduction in missed appointments were seen in self-testing patients. Positive patient satisfaction and lifestyle outcomes were identified through a telephone survey. A minority of patients struggled with the technique, leading to frustration. Some patients used many test strips through unsuccessful and additional tests. Conclusion: POC testing in a carefully selected group of patients on warfarin therapy resulted in positive clinical and patient satisfaction outcomes. Appropriate governance processes are needed, and clinical expertise is required to support patients. Cost-effectiveness of POC testing needs careful monitoring.